Sobrepeso y obesidad en los docentes de los colegios de la cabecera cantonal del cantón Paltas provincia de Loja durante el periodo marzo-agosto 2015 - Vargas Guamán, Darwin Manuel (2016)
Overweight and obesity are a health problem worldwide that has become increasingly important in recent years, being the root cause of these diseases, the energy imbalance between supply consumed and calories expended. The objectives of this research were; Identify the number of teachers / as overweight and obesity, assess to what degree of overweight and to what extent obesity are the / teachers as and analyze the major risk factors such as sedentary lifestyle, high-calorie diets and family history associated to overweight and obesity in / as teachers colleges Paltas Canton cantonal header. This scientific study is prospective, quantitative, transversal and field, a sample of 68 teachers / as was obtained, using weight and height to get the BMI, with the following results: 53% overweight and 47 % with obesity. Concluding that there as many overweight patients with road to obesity, as well as most are sedentary, with the consumer intake of energy-dense foods, and a predilection to overweight and obesity due to family history presented by certain teachers colleges of the Cantonal head of Canton Paltas province of Loja. Keywords: overweight, obesity